A novel hydrophobic all-biomass aerogel reinforced by dialdehyde carboxymethyl cellulose for oil/organic solvent-water separation. (3rd January 2022) - Zhang, Fengteng; Wang, Chunhua; Mu, Changdao; Lin, Wei
Abstract: We present a novel collagen-based hydrophobic aerogel for oil/water separation. The key feature of our approach is based on all-biomass materials, combined with effective crosslinking of collagen and dialdehyde carboxymethyl cellulose (DCMC) and hydrophobic coating by naturally derived waxes. The results show that the collagen with small amount of DCMC (∼0.25 wt%) under freezing and subsequent lyophilization can result in a spongy-like aerogel substrate with hierarchical structure and great reversible compressibility. The waxes coating not only maintains the interconnected porous structure, but also confers the micro/nano-scale wrinkling patterns on the resulting WC-Col aerogel surfaces. The hydrophobicity and lipophilicity of WC-Col aerogel is thus significantly improved as evidenced by a high contact angle of 144.4° and selective adsorption of oils from water. The repeated adsorption-squeezing tests demonstrate its reasonably good adsorption capacities and recyclability for varied oily liquids. Our study provides an ingenious approach to exploitation of biomass in pollutants removal. Graphical abstract: Image 1 Highlights: First study on fabricating of collagen-based superhydrophobic all-biomass aerogel. Cross-linking by minute DCMC can enhance the compressibility of aerogels markedly. Superhydrophobic conversion of amphiphilic surfaces is achieved by waxes coating. The aerogel shows high oil absorption capacity and reasonably good recyclability.